Respuesta :

Answer:

y = 141/44

Step-by-step explanation:

Solve for y:

(-47)/4 = (-11 y)/3

(-47)/4 = (-11 y)/3 is equivalent to (-11 y)/3 = (-47)/4:

(-11 y)/3 = -47/4

Multiply both sides of (-11 y)/3 = (-47)/4 by -3/11:

(-3 (-11) y)/(11×3) = (-3)/11×(-47)/4

(-3)/11×(-11)/3 = (-3 (-11))/(11×3):

(-3 (-11))/(11×3) y = (-3)/11×(-47)/4

(-3)/11×(-47)/4 = (-3 (-47))/(11×4):

(-3 (-11) y)/(11×3) = (-3 (-47))/(11×4)

(-11)/11 = (11 (-1))/11 = -1:

(-3-1 y)/3 = (-3 (-47))/(11×4)

(-3)/3 = (3 (-1))/3 = -1:

--1 y = (-3 (-47))/(11×4)

(-1)^2 = 1:

y = (-3 (-47))/(11×4)

11×4 = 44:

y = (-3 (-47))/44

-3 (-47) = 141:

Answer: y = 141/44